Kesesuaian Parameter Fisiko-Kimiawi Bagi Budidaya Rumput Laut Eucheuma Cottonii di Perairan Desa Leiting Kabupaten Kepulauan Aru - Laelaem, Agustina; Tuhumury, Semuel F.; Pattiasina, Bethsy J. (University of Pattimura, 2024)
Aru Islands Regency, especially in Sir-Sir Sub-district, there are several villages that are famous for their high potential seaweed resources, one of which is Leiting village. Eucheuma cottonii seaweed cultivation activities had stopped due to disease attacks. At present, the community of Leiting village wants to activate seaweed cultivation activities again, therefore it is necessary to assess the condition of the waters. This study aims to determine the physical-chemical parameters of the waters and analyse the suitability of these physical-chemical parameters for E. cottonii seaweed cultivation. Collection of data directly in the field includes physical-chemical parameters of the waters. Determination of the suitability of parameters for seaweed cultivation in the longline refers to Sirajudin (2009). The level of suitability was determined based on the suitability of physical-chemical parameters of waters for fish farming (Tiskiantoro, 2006). The study results show that the physical parameters of the waters include temperature range (27.20-28.07°C), salinity (28.99-29.61 ppt), brightness (2-4 metres), depth 2-4 metres, and the current strength 0.03-0.32 m/sec. While the range of water chemistry values includes pH (7.65-8.11), DO (6.85-9.52 mg/l), nitrate (0.131-0.153 mg/litre), phosphate (0.04-0.05 mg/litre), and Chlorophyll-a (0.72-3.61 mg/litre). The physico-chemical conditions in the waters of Leiting Village are still within the range of the quality standards for the development of seaweed cultivation. The results of the calculation of the suitability of waters in Leiting village found three consecutive suitability categories, which are very suitable (S1) of 12.24 hectares; conditionally suitable (S2) of 72.81 hectares and unsuitable (S3) of 11.98 hectares. So it can be concluded that seaweed cultivation activities are very feasible in the S1 area with a carrying capacity of 61 units and a capacity of 364 units are feasible in the S2 area.